SIKAP MASYARAKAT NELAYAN TERHADAP PEMENUHAN KEBUTUHAN KONSUMSI PANGAN DAN GIZINYA DI KECAMATAN SEMARANG UTARA KOTA SEMARANG - Puji Setyaningsih; Sutarto Sutarto (AGRITEXTS: Journal of Agricultural Extension, 2003)
The fulfillment of Food Consumption Needed and ifs nutrient that include: quality, quantity and food consumption and nutrient system, therefore, it needed sufficient. The lack or the excess of food will effected worn out to nutrient’s status and community health. The communities that become target of the research are fisherman that up till now they lacked get development priority directly that other community (farmer). Besides they also are a part of farmer's communities that are a subject or an object of development. And the final will influence of manpower resources 'quality closed related to the prosperity level and their work productivity. The difference of community environmental condition will influence to their nutrient condition to get or to consume. Food and nutrient needed. Therefore the fulfillment of food consumption and ifs nutrient's level suspended from their altitude to response and to apply in area life. The purpose of this research is to inspect the .fisherman's attitude to the fulfillment of food consumption and it's nutrient and based on quality, quantity and food consumption and its nutrient system in Semarang Utara Sub District Semarang City. The results of this research shows that analyze result of consumption needed are: food quality and respondent’s nutrient based on Sufficiency Variations Nutrient Value (NKRG) in high category (125,67%) and based on Difference Kind of Consumption Score (B.JK) 55 % medium category, 22 % sufficient category, and 23 % low category, food consumption quantity and its nutrient shows that each value of Sufficiency Nutrient Level ([KG) different. If the quantity category assumed same with NKRG categorization, therefore to energy value, protein, zinc, vitamin A, riboflavin ,and vitamin C in high category (80%), thiamin and niacin in medium category (70-80%) and for calcium in low category (<60 %), while to food consumption and its nutrient reach 84,8 in high category. This result becomes answering standard of that attitude. Fisherman's attitudes lo the fulfillment of food consumption and its nutrient need -from the quality aspect, quantity bad consumption, system usually in high category. It could observe practically (psychomotor aspect and affective aspect). And by theoretical (cognitive aspect) is very low 90 % respondent do not have a good nutrient knowledge.